KEMAMPUAN VO2 MAX WASIT HOCKEY PUTERI LISENSI TINGKAT DASAR DI KOTA SURABAYA - AGUS ABRIANTO, TOMI Agus (Jurnal Prestasi Olahraga, 2013)
VO2 max is the maximum volume of oxigen is processed by the body during intense activity. Volume and a level of ability of the body which is expressed in liters per minute or milliliter / minute / kg body weight. A hockey referee should have a good level of physical fitness in accordance with the International Hockey Federation so that each lead of a game can run well. The purpose of this study was to determine the level of princess hockey referee VO2 max base level license in the city of Surabaya which has been carrying out a basic level hockey referee upgrading in 2009. Based on the results of research carried out by using MFT to determine VO2 max level hockey referee license daughter of a basic level, the percentage of data is known hockey referee daughter of a basic level license in the city of Surabaya, which has good levels of VO2 max criterion does not exist at all categorized so that all the less, hockey referee who either do not qualify as any of 11 the number of female hockey referee license in the city of Surabaya basic level or 0% while the female hockey referee who entered on the poor criteria there were 11 people from 11 the number of female hockey referee license in the city of Surabaya basic level or 100% of the total number of referees. By knowing the results of this study, it can provide data and information for Hockey Federation Indonesia (FHI) in Surabaya to determine the extent of female hockey referee VO2 max base level license in the city of Surabaya who already have a basic level hockey referee certificates. Key words: VO2 Max, Miss Hockey Referee, the Basic